Identificação de ambientes bioclimáticos na Bacia Hidrográfica do Alto rio Paraíba, PB, Brasil - Macêdo, Mônica Larissa Aires de (2020)
This research intends to present a proposal for a descriptive model of bioclimatic environments that can uses three variables (soil water storage, potential evapotranspiration and pluviometry) and can be applied in geographically diverse areas. Using Geographic Information Systems (GIS's) and the programming language in R, it was possible to characterize and spatially integrate the model variables, the main subject of this research, the same procedures were used, as well as combinatorial simple. Based on the criterion of water availability to plants, with the combination of data a classification was obtained with two categorical levels, class and subclass of environments. The classes from A to E are defined by the degree of water limitation, while the subclasses, expressed by numerical indices from 1 to 5, specify the contributions of the limitations exercised by each parameter of the model. From the analysis of the results, it can be concluded that relief, although not very active, has a notable influence on the spatial distribution of the variables studied. A low average annual range of thermal variation was observed, predominantly between 22 °C and 24 °C. The annual rainfall varied from 300 mm to 800 mm, spreading gradually from west to obeying the slope of the drainage. The synthesis map of bioclimatic environments led to 5 classes and 43 subclasses. From classes A to E, areas between 25 and 2449 km2 were defined. Class E was considered to have a very high degree of water limitation, where the temperature in is very high due to drainage depression. Conversely, class A was classified with a very low degree of limitation, occurring in more favorable conditions of precipitation and evapotranspiration, in about 25 km2 (0.4%). Finally, it is worth noting that despite the existing limitations the results obtained were less generalist since they allowed the identification of landscapes and their potential, a fact that is expected to provide adequate support for future research.